2023
DOI: 10.3389/fneur.2023.1288150
|View full text |Cite
|
Sign up to set email alerts
|

Treatment efficacy of repositioning maneuvers in multiple canal benign paroxysmal positional vertigo: a systematic review and meta-analysis

Mohamad Alfarghal,
Niraj Kumar Singh,
Mohammed Abdullah Algarni
et al.

Abstract: IntroductionBenign paroxysmal positional vertigo (BPPV) involving the posterior canal is more common than other canals; however, simultaneous involvement of multiple canals can be seen up to 20% of all BPPV cases. The diagnosis and management of multiple canal BPPV can be quite challenging due to the complexity of findings. Therefore, this systematic review and meta-analysis aimed at unveiling the most effective repositioning strategy for the treatment of multiple canal BPPV.MethodsA literature search through … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 81 publications
0
2
0
Order By: Relevance
“…VRT is another treatment option that can be effective in improving balance and reducing dizziness in patients with BPPV and with affected quality of life [33,34]. VRT involves a series of exercises designed to promote central nervous system compensation for inner ear deficits and improve overall vestibular function [33,34].…”
Section: Chinamentioning
confidence: 99%
See 1 more Smart Citation
“…VRT is another treatment option that can be effective in improving balance and reducing dizziness in patients with BPPV and with affected quality of life [33,34]. VRT involves a series of exercises designed to promote central nervous system compensation for inner ear deficits and improve overall vestibular function [33,34].…”
Section: Chinamentioning
confidence: 99%
“…VRT is another treatment option that can be effective in improving balance and reducing dizziness in patients with BPPV and with affected quality of life [33,34]. VRT involves a series of exercises designed to promote central nervous system compensation for inner ear deficits and improve overall vestibular function [33,34]. Studies have shown that VRT can lead to significant improvements in symptoms, which include unsteadiness and fear of falling, which can affect the quality of life for patients with BPPV [33,34].…”
Section: Chinamentioning
confidence: 99%